2007
DOI: 10.1167/iovs.06-1332
|View full text |Cite
|
Sign up to set email alerts
|

American Chinese Glaucoma Imaging Study: A Comparison of the Optic Disc and Retinal Nerve Fiber Layer in Detecting Glaucomatous Damage

Abstract: The RNFL showed a stronger structure-function association and a higher diagnostic sensitivity for glaucoma detection than did the neuroretinal rim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…As compression on the axons is relieved by IOP reduction, the axons may recover their normal shape and size, with resultant increase in RNFL thickness without changes in ONH parameters. These findings could be explained by the fact that the RNFL is a more direct measure of the integrity of retinal ganglion cells, in contrast to the neuroretinal rim, which is composed of nerve fiber bundles, glial cells, and connective tissues 21 and could explain the presence of a statistically significant change for RNFL but not for ONH in our series. However, data interpretation deserves high caution because they could be also explained by physics rules.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Almentioning
confidence: 58%
See 1 more Smart Citation
“…As compression on the axons is relieved by IOP reduction, the axons may recover their normal shape and size, with resultant increase in RNFL thickness without changes in ONH parameters. These findings could be explained by the fact that the RNFL is a more direct measure of the integrity of retinal ganglion cells, in contrast to the neuroretinal rim, which is composed of nerve fiber bundles, glial cells, and connective tissues 21 and could explain the presence of a statistically significant change for RNFL but not for ONH in our series. However, data interpretation deserves high caution because they could be also explained by physics rules.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Almentioning
confidence: 58%
“…Besides, RNFL attained a higher value in the change of visual sensitivity with respect to different levels of structural damage compared with neuroretinal rim measures. 21 The availability of the elements for a correct sample size calculation was limited by the lack of homogenous data on the effect of sudden IOP reduction on RNFL. We assumed that a change of mean RNFL thickness, as occurring between middle and advanced glaucoma, could be clinically significant.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Almentioning
confidence: 99%
“…[16][17][18] A recent study reported that RNFLT with a second order polynomial regression model fit had the highest correlation (R 2 = 0.383) with MD, better than with rim area measured by HRT. 18 Our results are consistent with this study in that RNFLT could be a more sensitive structural parameter to capture visual function loss in glaucoma than global changes in the ONH.…”
Section: Discussionmentioning
confidence: 98%
“…The RNFL defect may precede detectable changes on the optic disc and visual field (VF), 11 and RNFL-based assessments have been reported to be superior to optic disc-based assessments for the diagnosis of glaucoma. 12,13 Although both diseases accompany loss of RNFL, the underlying pathophysiologies of the two diseases are different. Structurally, RNFL loss in diabetes shows a relatively low correlation with the corresponding optic disc area compared to glaucoma, in which rim thinning in the optic disc corresponds to RNFL loss.…”
mentioning
confidence: 99%